Impact of rhythm in non-valvular atrial fibrillation on four cardiac chamber deformation imaging. (25th November 2020) - Philabout, P; Soulat-Dufour, L; Benhamou-Tarallo, I; Lang, S; Ederhy, S; Ancedy, Y; Adavane-Scheuble, S; Chauvet-Droit, M; Nhan, P; Jean, M; Ben Said, R; Boccara, F; et al.
Abstract: Background: Few studies have assessed the evolution of cardiac chambers deformation imaging in patients with atrial fibrillation (AF) according to cardiac rhythm outcome. Purpose: To evaluate cardiac chamber deformation imaging in patients admitted for AF and the evolution at 6-month follow-up (M6). Methods: In forty-one consecutive patients hospitalised for AF two-dimensional transthoracic echocardiography was performed at admission (M0) and after six months (M6) of follow up. In addition to the usual parameters of chamber size and function, chamber deformation imaging was obtained including global left atrium (LA) and right atrium (RA) reservoir strain, global left ventricular (LV) and right ventricular (RV) free wall longitudinal strain. Patients were divided into three groups according to their cardiac rhythm at M0 and M6: AF at M0 and sinus rhythm (SR) at M6 (AF-SR) (n=23), AF at M0 and AF at M6 (AF-AF) (n=11), SR at M0 (spontaneous conversion before the first echocardiography exam) and SR in M6 (SR-SR) (n=7) Results: In comparison with SR patients (n=7), at M0, AF patients (n=34)) had lower global LA reservoir strain (+5.2 (+0.4 to 12.8) versus +33.2 (+27.0 to +51.5)%; p<0.001), lower global RA reservoir strain (+8.6 (−5.4 to 11.6) versus +24.3 (+12.3 to +44.9)%; p<0.001), lower global LV longitudinal strain (respectively −12.8 (−15.2 to −10.4) versus −19.1 (−21.8 to −18.3)%; p<0.001) and lower global RV longitudinal strain (respectively −14.2 (−17.3 to −10.7) versus −23.8 (−31.1 to −16.2)%; p=0.001). When compared with the AF-SR group at M0 the AF-AF group had no significant differences with regard to global LA and RA reservoir strain, global LV and RV longitudinal strain (Table). Between M0 and M6 there was a significant improvement in global longitudinal strain of the four chambers in the AF-SR group whereas no improvements were noted in the AF-AF and SR-SR group (Figure). Conclusion: Initial atrial and ventricular deformations were not associated with rhythm outcome at six-month follow up in AF. The improvement in strain in all four chambers strain suggests global reverse remodelling all cardiac cavities with the restoration of sinus rhythm. Funding Acknowledgement: Type of funding source: None